Friction (Grand Central Publishing, 2015)
A Texas Ranger, relegated to desk work due to past recklessness, petitions to regain custody of his five-year-old daughter, and his case is assigned to a family court judge who is as attractive as she is ambitious. When a masked gunman barges in during the custody hearing with his sights on the judge, the Ranger reacts instinctually and goes after him. But authorities apprehend the wrong man, and the real gunman remains unknown, at large, and a threat. Will this take-charge lawman jeopardize his chances of custody by going after the would-be assassin? And will this unlikely pair be able to deny the forbidden attraction building between them?

A gift of grace (Kauffman Amish bakery, 1,, 2009)
When Rebecca Kauffman's sister Grace, who left the Amish behind years earlier, is killed in an accident, it is up to Rebecca and her husband Daniel to raise Grace's two teenage English daughters in their Old Order Amish community.

Amber Brown is green with envy (G. P. Putnam's Sons, 2003)
Fourth-grader Amber Brown must make some important decisions when her mother and Max move their wedding date up and prepare to buy a house together, while her father makes some bad choices of his own.

Like Dandelion Dust (Warner Faith, Center Street, 2006)
Description Not Provided